Analysis of Income and Factors Affecting Farmers' Decisions to Join Corporate Farming (Case Study: Tawangsari District, Sukoharjo Regency) - Apriyani, Duwi -; Falatehan, A Faroby; Surahman, Memen (JURNAL MANAJEMEN AGRIBISNIS, 2021)
The Government of Sukoharjo District established a corporate farming program in Dalangan, Tawangsari District, Sukoharjo Regency since 2017 as an example of early development of agriculture modern in the countryside. However, the program has not run continuously due to constraints capital and has a high dependence on the decisions of decision makers. The objectives of this stud y are: (1) to identify farmers’ perceptions of corporate farming programs; (2) identifying and analyzing the importance and influence of corporate farming in Dalangan, Tawangsari District, Sukoharjo Regency; (3) analyze the impact of the application of corporate farming on the income of member farmers and not members of the corporate farming ; and (4) analyze the level of influence of farmer characteristic fac tors on the decision to follow corporate farming . Data analysis methods used were des criptive analysis, stakeholder analysis , R / C ratio income analysis, and binomial logistic regression analysis. The results showed that the majority of farmer respondents agreed that the implementation of farmer corporations in Dalangan could improve farm performance, but the corporate farming had not made it easier for farmers to access Gapoktan capital. Based on stakeholder analysis, the Agriculture Service of Sukoharjo Regency and Gapoktan Tani Mandiri have the highest level of importance and influence in implementing the corporate farming . Based on income analysis, the value of R / C ratio and B / C ratio for cash costs to member farmers and not members of corporate farming is more than 1, so farming in groups is profitable and feasible. Factors that influence farmers' decisions to follow the corporate farming , namely the number of family dependents and farm income.